Histological study of SlNPV infection on body weight and peritrophic membrane damage of Spodoptera litura larvae - YAYAN SANJAYA; DADANG MACHMUDIN; NANIN DIAH KURNIAWATI (Nusantara Bioscience, 2010)
Abstract. Sanjaya Y, Machmudin D, Kurniawati ND. 2010. Histological study of SlNPV infection on body weight and peritrophic membrane damage of Spodoptera litura larvae. Nusantara Bioscience 2: 135-140. The effect of SlNPV infection on body weight and peritrophic membrane damage of Spodoptera litura Fab. larvae has been carried out. The method was used Probit analysis, and based on LD 50 the virus was infected to know body weight and post-infection damage.The damage of histological structure caused by SlNPV (0, 315, 390, 465, 540 dan 615 PIB/mL) was investigated after 0, 12, 24, 72 and 96 hours post infection. The histological material was prepared by using paraffin method after fixation with Bouin Solution, then slice into 7 um and colored with Hematoxylin-Eosin. The result showed that the exposure SlNPV cause decreasing food consumption especially on 540 PIB/mL give average rate as amount of 0.1675 mg. The descriptive observation on structural intact of peritrophic membrane histology caused by SlNPV infection shows a tendency to decrease, while in control, there was no damage at all. The longer the exposition of virion in the midgut lumen the more damage on peritrophic membrane occurred. The severest damage occurred 96 hours after infection. The result proves that haNPV virion can destroy histological structure of midgut.